2019
DOI: 10.1016/j.alcr.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sexual norms and college sexual experiences: Do high school norms influence college behavior?

Abstract: Research on adolescent and young adult sexuality typically does not examine how social norms and other messages learned in adolescence may impact sexual behavior in emerging adulthood. This research uses a life course framework to examine how social norms about sexuality in high school influence subsequent sexual behavior within university cultures promoting casual sex. Forty-five semi-structured interviews were conducted with undergraduate women on a large public Western United States university campus. Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(96 reference statements)
0
4
1
Order By: Relevance
“…Similarly, the present study revealed that awareness of sexual intercourse among peers significantly increases the probability of engaging in sexual intercourse although the causality is not clear as this is contrary to the majority of existing literature globally [9,25]. However, few studies have concluded that the close environment and neighbourhood which induce or promote premarital or casual sexual relationships, could encourage the youth within the said neighbourhood to practice the same [26][27][28].…”
Section: Discussioncontrasting
confidence: 66%
“…Similarly, the present study revealed that awareness of sexual intercourse among peers significantly increases the probability of engaging in sexual intercourse although the causality is not clear as this is contrary to the majority of existing literature globally [9,25]. However, few studies have concluded that the close environment and neighbourhood which induce or promote premarital or casual sexual relationships, could encourage the youth within the said neighbourhood to practice the same [26][27][28].…”
Section: Discussioncontrasting
confidence: 66%
“…Research on CSRs, conducted primarily in North-American countries, has identified a script for casual sex that encompasses specific behaviors, interactions, and contexts (Epstein et al, 2009;Olmstead et al, 2019) and is associated with a "hook-up culture" that has become socially established on university campuses as an expression of the normative and even compulsory nature of casual sex among university students (Bogle, 2008;Wade, 2017). Even though not all emerging adults engage in the campus-based hookup culture, such as those who do not attend college, those who are in a monogamous relationship, or those who choose to prioritize their studies and opt out, 60-80% of North-American college students report having been involved in at least one casual sexual relationship (Garcia et al, 2012;James-Hawkins, 2019). Although hookup scripts contain some distinctive components (e.g., Eaton and Rose, 2012;Olmstead et al, 2019), they are more varied and complex than dating scripts (Bogle, 2008;Heldman and Wade, 2010), making it more difficult to predict the pathways of the relationship (Allison, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The life course perspective posits that experiences at one stage of life will have an impact on later stages of life (Bernardi, Hiunink, & Settersten, 2019;Elder, 1994), suggesting that the onset of the transition to adulthood starts with first sexual experiences (James-Hawkins, 2019). The sexual debut, in particular, represents a life-changing event that looms large in the memories and lives of teenagers (Brown, 1999; and can have profound direct and indirect influences on later family life courses (Manning, Giordano, & Longmore, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the role that the family of origin plays for children's timing and type (protected or unprotected) of sexual debut. Parents express both explicit and implicit messages about sexuality to their children (Mollborn, 2017), and while norms about sexuality can vary in relation to changing social networks (James-Hawkins, 2019), parents continue to have a large influence on their offspring's sexuality (Mancin & Dalla Zuanna, 2004). We consider a fundamental characteristic of the family of origin: parental socioeconomic status (SES), i.e., parental education and social class.…”
Section: Introductionmentioning
confidence: 99%